Effect of Nitrogen and Phosphorus on Yield Attributes, Seed Yield and Oil Content of Irrigated Safflower in Laterite Soil - Zaman, A (Annals of Arid Zone, 2016)
Effect of nitrogen (0, 60 and 120 kgfha) and phosphorus (O, 40 and 80 kg/ha) on the performance of safflower in laterite soil was studied. Application of 120 kg N and 40 kg P205/ha significantly improved the growth and yield components and increased the seed yield of safflower. Oil percentage in seeds reduced significantly with nitrogen more than 60 kg/ha but higher levels of phosphorus improved the oil content.